NGAL, MIC-1 and CA19-9 in Pancreatic Juice: Pathobiological Implications in Diagnosing Benign and Malignant Disease of the Pancreas - KAUR, SUKHWINDER (2013)
OBJECTIVE: Pancreatic diseases pose significant diagnostic challenge as signs and symptoms often overlap. We investigated the potential of pancreatic juice neutrophil gelatinase–associated lipocalin (NGAL), macrophage inhibitory cytokine-1 (MIC-1), and carbohydrate antigen 19-9 (CA19-9) to aid in the diagnosis of patients with symptoms suggestive of pancreatic diseases. METHODS: 105 chronic pancreatitis (CP), pancreatic cancer (PC), and non-pancreatic non-healthy (NPNH, patients with symptoms mimicking pancreatic disease but found to be free of pancreatic pathology) patients underwent endoscopic pancreatic juice collection following secretin-stimulation. NGAL and MIC-1 levels were measured by enzyme-linked immunosorbent assay while CA19-9 was measured by radioimmunoassay. RESULTS: NGAL, MIC-1, and CA19-9 were significantly elevated in the pancreatic juice of CP and PC patients as compared to NPNH controls (p<0.034). NGAL appeared most promising in differentiating diseased versus non-diseased pancreata (AUCs=0.88–0.91) while MIC-1 was found to be higher in PC than CP patients (p=0.043). Interestingly, MIC-1 levels in diabetic PC patients were higher than in non-diabetic PC (p=0.030) and diabetic CP patients (p=0.087). CA19-9 showed the least ability to distinguish patient groups (AUCs=0.61–0.76). CONCLUSIONS: Pancreatic juice NGAL shows potential utility in establishing pancreatic etiology in the context of non-specific symptoms while MIC-1 may aid in differentiating PC from CP.